Assessment of onshore wind energy potential under temperate continental climate conditions. (August 2022) - Paraschiv, Spiru; Paraschiv, Lizica Simona; Serban, Alexandru; Cristea, Anisoara Gabriela
Abstract: Using the Weibull distribution function, the study presents a statistical evaluation of wind characteristics and onshore wind power potential under temperate continental climate conditions. Wind energy projects are more expensive to install than conventional energy sources, but they have lower operating and maintenance costs (zero costs for fuel). Because the initial investment is so large, conducting as precise and reliable feasibility studies as possible is critical because they play a significant role in lowering the cost of energy production. As a result, wind speed measurements are critical for conducting accurate feasibility studies. The availability and accuracy of weather data are critical for determining wind potential at a specific location. Wind speed is an important factor to consider when analyzing the wind speed distribution function. The monthly and yearly values of Weibull parameters, and wind power density at the analyzed location, were estimated using wind speed data. The yearly value of the k parameter for the Weibull analysis was 1.153, and for the c parameter was 5.602, respectively. Also, the yearly average wind speed was found to be greater than the maximum wind speed. Another important conclusion is that the maximum energy-producing wind speed, rather than the average or most frequent wind speed, has the greatest influence on wind potential. The final outcome of this study indicate that the location analyzed is adequate for the exploitation of wind energy.